A Broadband Left-Handed Metamaterial Microstrip Antenna with Double-Fractal Layers - Roman Kubacki; Salim Lamari; Mirosław Czyżewski; Dariusz Laskowski (International Journal of Antennas and Propagation)
This paper proposes a microstrip patch antenna based on the left-handed metamaterial concept, using planar periodic geometry, which results in improved characteristics. This periodic geometry is derived from fractal shapes, which have been widely used in antenna engineering. The metamaterial property was obtained as a result of the double-fractal structure on both the upper and the bottom sides of the antenna. The final structure has been optimized to enhance bandwidth, gain, and radiation characteristics of the microstrip antenna. This combination significantly improved antenna performance; our design could support an ultrawide bandwidth ranging from 4.1 to 19.4 GHz, demonstrating higher gain with an average value of 6 dBi over the frequency range and a peak of 10.9 dBi and a radiation capability directed in the horizontal plane of the antenna.